Dialogue Between Theology and Science: Present Challenges and Future Perspectives - Giuseppe Tanzella-Nitti (Religions)
In order to consider the natural sciences as a contemporary locus theologicus, I here examine the meaning and implications of the “dialogue between theology and the sciences”. Although widely used, this expression has different meanings. I try to clarify who the interlocutors of the dialogue are, where the dialogue takes place, and what the goals of the dialogue itself are. A coherent agenda to encourage the use of the sciences in theological work should include (a) the design and implementation of interdisciplinary curricula to help those scholars who are seriously interested to be trained in this field; (b) an emphasis on the role of philosophy and philosophical sources in the study of the sciences and theology; (c) going beyond the epistemological level and developing the dialogue also at the anthropological level; (d) the identification of a number of key issues for theological and religious studies that are expected to become more urgent in the coming years. Finally, the use of the sciences as a locus theologicus is expected to bear two main fruits: first, to offer a positive, speculative insight to the work of theologians and, second, to contribute to a responsible development of the dogmatic teachings of the Church.